2021
DOI: 10.3390/pharmaceutics13030359
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Respiratory Toxicity of Protamine Sulfate in Zebrafish and Rodent Models

Abstract: Protamine sulfate (PS) is the only available option to reverse the anticoagulant activity of unfractionated heparin (UFH), however it can cause cardiovascular and respiratory complications. We explored the toxicity of PS and its complexes with UFH in zebrafish, rats, and mice. The involvement of nitric oxide (NO) in the above effects was investigated. Concentration–dependent lethality, morphological defects, and decrease in heart rate (HR) were observed in zebrafish larvae. PS affected HR, blood pressure, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…We and others previously reported that polycations may induce lung congestion [ 49 ] and mononuclear cell infiltration [ 50 ]. PS impaired heart tissue, and it was previously reported to alter the cardiac function of zebrafish and the heart rate of rats [ 51 ] by directly affecting myocyte contractile functions [ 52 , 53 ]. We have also found some histological changes in the brain, the spleen, and other organs that occurred in all animals, including in the vehicle group, indicating that they were related to the experimental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…We and others previously reported that polycations may induce lung congestion [ 49 ] and mononuclear cell infiltration [ 50 ]. PS impaired heart tissue, and it was previously reported to alter the cardiac function of zebrafish and the heart rate of rats [ 51 ] by directly affecting myocyte contractile functions [ 52 , 53 ]. We have also found some histological changes in the brain, the spleen, and other organs that occurred in all animals, including in the vehicle group, indicating that they were related to the experimental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still issues limiting their usefulness. Protamine may interact with clotting [16][17][18], which makes it unsuitable for in vitro neutralization tests. A heparinase requires a lengthy preparation of a plasma sample [7,12].…”
Section: Introductionmentioning
confidence: 99%